2018
DOI: 10.1177/2331216518759214
|View full text |Cite
|
Sign up to set email alerts
|

Music Training Can Improve Music and Speech Perception in Pediatric Mandarin-Speaking Cochlear Implant Users

Abstract: Due to limited spectral resolution, cochlear implants (CIs) do not convey pitch information very well. Pitch cues are important for perception of music and tonal language; it is possible that music training may improve performance in both listening tasks. In this study, we investigated music training outcomes in terms of perception of music, lexical tones, and sentences in 22 young (4.8 to 9.3 years old), prelingually deaf Mandarin-speaking CI users. Music perception was measured using a melodic contour identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 49 publications
(122 reference statements)
1
42
0
1
Order By: Relevance
“…The participants consisted of both adult and pediatric patients with hearing loss who had been fitted with hearing aids and cochlear implants. The age of the 101 adult participants who had consistently used hearing aids before post-lingual cochlear implantation [16][17][18][19] ranged from 18 to 88 years old, and the age of the 85 children ranged from 1 to 15 years old [20][21][22][23][24][25]. Among the participants, 89 were female and 76 were male; however, the sex of 21 participants in two studies by Fuller et al [16] and Yucel et al [23] was not specified.…”
Section: Characteristics Of Studies In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The participants consisted of both adult and pediatric patients with hearing loss who had been fitted with hearing aids and cochlear implants. The age of the 101 adult participants who had consistently used hearing aids before post-lingual cochlear implantation [16][17][18][19] ranged from 18 to 88 years old, and the age of the 85 children ranged from 1 to 15 years old [20][21][22][23][24][25]. Among the participants, 89 were female and 76 were male; however, the sex of 21 participants in two studies by Fuller et al [16] and Yucel et al [23] was not specified.…”
Section: Characteristics Of Studies In the Meta-analysismentioning
confidence: 99%
“…The overall mean PE-Dro score was 6.5. The quality of the articles ranged from fair to good, with the quality of two studies being assessed as fair [18,24] and the quality of the remaining studies classified as good [16,17,[19][20][21][22][23]25] due to a lack of information about the random allocation of subjects, the blinding process, and whether the key outcome were analyzed by "intention-to-treat" or not.…”
Section: Training Periodmentioning
confidence: 99%
“…Previous research examining short-term music training have reported positive hearing outcomes in CI users (see review by Gfeller, 2016). For instance, training on melodic contour identification or pitch patterns has been shown to improve CI users' sensitivity to pitch pattern perception, and/or music and speech perception (Galvin et al, 2009;Fu et al, 2015;Lo et al, 2015;Smith et al, 2017;Cheng et al, 2018). Other music training approaches (e.g., playing, singing, listening to music) can also improve music and speech perception (Gfeller et al, 2015;Good et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies on music training, however, reported the facilitating role of music training in improving CI users' perceptual ability in pitch-related tasks (J. K.-C. Chen et al, 2010; Cheng et al, 2018; Fu et al, 2015; Gfeller, 2016; Polonenko, Giannantonio, Papsin, Marsella, & Gordon, 2017; Torppa et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…More recently, there has been an increasing interest in the effects of music training on speech and music perception in CI users (Abdi, Khalessi, Khorsandi, & Gholami, 2001; J. K.-C. Chen et al, 2010; Cheng et al, 2018; Fu, Galvin, Wang, & Wu, 2015; Innes-Brown, Marozeau, Storey, & Blamey, 2013; Torppa et al, 2014; Yucel, Sennaroglu, & Belgin, 2009). For example, J.…”
Section: Music Training On Pitch Perception In Children With Cismentioning
confidence: 99%